Matharpacady-27.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The patron saint of the Holy Cross is St. Roch, who is especially invoked against plague, cholera, and epidemics. Traditionally, every year, the Managing Committee of the Holy Cross Oratory organizes the nine-day Novena Services, which are held in the late evening from April 22 to April 30. This is the stained glass portrait of Jesus Christ on the rose window of the chapel, illuminated during Christmas.